Lumbar Sympathetic Block for Intractable Lower-Limb Postherpetic Neuralgia: Report of Two Cases - ÖZTÜRK, EKİM CAN; GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (WILEY, 2021)
Lumbar sympathetic block is a commonly used technique for sympathetically mediated pain syndromes. Postherpetic neuralgia (PHN) is also accepted to be associated with sympathetic system activation. While sympathetic blocks were utilized for upper-extremity or face-related PHN, there has not been any report regarding lower-extremity PHN, as it is an uncommon region. Here, we present two cases of systemic drug-resistant PHN in lower limb, relieved with lumbar sympathetic block. Both patients had at least 50% reduction in numeric rating scale (NRS) scores at the end of 6 months. Lumbar sympathetic block could be considered in the treatment of lower-limb PHN. More reports and controlled trials are needed for further understanding the role of the intervention in this neuropathic pain syndrome.
Keywords: lumbar sympathetic block; postherpetic neuralgia; neuropathic pain; HERPES-ZOSTER; GANGLION